Fisheries Business Management In The Globalization Era - Kurniawan, Zuki (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2023)
The fishing business is the process of managing and optimizing fishery resources to generate sustainable profits. The fisheries business includes everything related to fishing, fish farming, fish processing, and distribution of fish products to the market. In the fishing business, it is important to consider factors such as economic, social, and environmental factors. Economic aspects include production costs, selling prices, and business profitability. Social aspects include the welfare of fishermen, food security, and the interests of the surrounding community. Environmental aspects include conservation of natural resources and environmental management to minimize negative impacts on ecosystems. Good fisheries business management requires careful planning and strategy, the use of the latest technology and methods, as well as cooperation between related parties. A sustainable fishing business aims to create a balance between economic profit, environmental sustainability, and social welfare.